Educational Technologies for patients and family in Palliative Care: An integrative review (Research, Society and Development, 2021)
Educational technologies are tools that help transmit knowledge and can be used in different contexts. Given its potential to resolve doubts and develop skills, this research aimed to identify scientific evidence in the literature about the use of educational technologies on palliative care designed for cancer patients and their families. This is an integrative literature review, with the following PICo strategy: “What educational technologies (I) are being developed on Palliative Care (Co) for patients and their families (P)?”. The established time frame comprised the period from 2015 to 2021, in the MEDLINE databases via National Library of Medicine National Institutes of Health (PubMed), Literatura Latino Americana e do Caribe em Ciências da Saúde (LILACS), Scientific Electronic Library Online (SCIELO) and in the Nursing Database (BDENF) via the Biblioteca Virtual em Saúde (BVS). The Health Sciences Descriptors (Decs/MESH) “educational technology”, “Health Education”, “caregivers”, “patients” and “Palliative Care” in Portuguese, English and Spanish were used. The interaction of descriptors was performed by the Boolean operators AND and OR. 14 studies were selected. Through the analysis, it was possible to divide into four categories that evidenced technologies aimed at concepts and guidelines of care, for caring for the caregiver, to assist in decision making and to aid communication. It is concluded, therefore, that educational technologies are important tools to assist in the education process, helping professionals to introduce the subjects and also serving as a source of consultation in times of doubts and uncertainties. It is necessary to develop different technologies that consider the different age groups, specificities involving regionality and cultural diversities.